PESANTREN TANWIRUL HIJA SUMENEP DALAM MENGHADAPI TANTANGAN GLOBAL - Aksin Wijaya (Institut Agama Islam Negeri Madura, 2015)
In the world of science, the institutions of education have become the foundation of educators to teach science for the next generation. Pesantren (Islamic boarding school) is the oldest traditional educational institutions, which still exists in Indonesia until now. It is in this institution in which islamic scholars transform Islamic knowledge to society. Globalization has influenced the world of edu-cation, wherever it comes from, including pesantren.This paper discusses the role of boarding schools in educating students so that they not only able to face the challenges of globalization, but also guard their identity as islamic students (santri), in three main discussion: first, how the existence, essence and role of the boarding school in facing the changing times are; second, how the boarding schools face the future; and third, as an example, how pesantren of Tanwirul Hija in Sumenep, Madura changes to face the challenges of globalization. This study concludes that in order to deal with global challenges, pesantren has been continually maintaining the essence of the islamic boarding school, while at the same time appreciating the new educational methods that lead to the inclu-siveness and gender awareness. By standing on two feet, the boarding schools, including Tanwirul Hija, not only exists but also will be able to create new cadres who are ready to compete with other competitors from any different institutions, both in the islamic knowledge and general sciences. In short, reforms in all areas of pesantren, which is the focus of this paper, are absolutely done.Copyright (c) 2015 by KARSA. All right reservedDOI: 10.19105/karsa.v23i2.725